Digital Transformation In Da'wah Management: A Strategic Framework For Enhancing Public Engagement In The Post-Truth Era - Dudun Ubaedullah; Imam Khairul Annas; Muhammad Fatih Azka; Nurkholis Nuri (Cv. Kayaswara, Indonesia, 2026)
Purpose of the study: This study aimed to formulate an adaptive, ethical, and participatory strategic framework for digital da'wah management to address the challenges of the post-truth era, characterized by the proliferation of disinformation, religious hoaxes, and the weakening of traditional religious authority in digital spaces. Methodology: A Systematic Literature Review using the PRISMA approach was applied, involving the retrieval of Scopus-indexed articles and Sinta-accredited national journals published between 2015 and 2025. Of the 312 initially identified articles, 38 articles met the inclusion criteria and were analyzed using thematic analysis. Main Findings: The digital transformation of da'wah operates through five interrelated strategic dimensions: digital leadership, media literacy, content management, a collaborative ecosystem, and prophetic communication ethics. The resulting strategic framework emphasizes integrating tabayyun values, religious moderation, and message personalization to strengthen public engagement. Novelty/Originality of this study: The novelty lies in the integration of five strategic dimensions digital leadership, media literacy, content management, collaborative ecosystems, and prophetic communication ethics into a single evidence-based, collaborative framework for digital da'wah management specifically designed to address the post-truth era, an approach not previously documented in the context of strengthening sustainable public trust in religious da'wah organizations.